Stargazing Under Suburban Skies A Star-Hopper's Guide - Zack, Malcolm (The Patrick Moore Practical Astronomy Series,, 2018)
Anyone interested in astronomy battles with the conveniences of modern living - street lights, advertising and security lighting, tall buildings, and even the occasional tree. More than 85% of the population now lives in crowded and light-polluted towns and cities. This book is for those who live in or near towns and cities and own relatively modest equipment, although observers with larger instruments will still find many of the target objects of interest. The book encourages the use of star-hopping techniques to find objects in the night sky. Included is a list of 100 popular deep sky objects, ranked according to how difficult they are to find. Each object is described and has companion star-hopping charts, images and sometimes sketches. As a result, readers can gain a sense of their own backyard view from Earth. There is also a top 30 list of lunar objects, a section on planetary observing, annotated lists of popular astronomy apps and software, and tips on how to make the most of your location. Stargazing Under Suburban Skies: A Star-Hopper's Guide is the essential companion to what can be seen and how, regardless of the obstacles.